DAMPAK KOPERASI TERHADAP PEREKONOMIAN MASYARAKAT JORONG PADANG BINTUNGAN KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - LESTARI, FEBRI - (Pendidikan Sosiologi, 2014)
The purpose of this research are : 1) to describes the factors that causes KUD operation is not active, 2) to describes the function of koperasi, 3) to describes the impact of koperasi in Jorong Padang Bintungan, Kecamatan Koto Baru, Kabupaten Dharmasraya. The research utilize kualitatifâs approaching with descriptive type. The location of this research in Jorong Padang Bintungan. The total informants of this research are 12 people, consist of 4 koperasi organizers, and 8 koperasi koperasi members. The instruments of this research are interview and document. Analisis is data utilizes model Milles and Huberman, consist of data collection, data reduction, interpest the data, and taking final conclusion of the data. Result of this research are : first, factor that causes koperasi is not active, 1) loans is not returned, 2) difficult to collect this loads, 3) deposit is not paid. Second, the functions of KUD Sidorejo are: 1) providers of capital working, 2) providers of agricultural fertilizers, 3) providers of primary necessities, 4) providers of agricultural equipments. Third, the impact of KUD forward sosio-economy life of societies. 1) agricultural product decreased, 2) low income of society, 3) primary necessities are expensive, 4) rental agricultural equipments are expensive.